AKTIVITAS SISWA DALAM MENYELESAIKAN MASALAH SEHARI HARI YANG MELIBATKAN SPLDV - Nasrun, Hasnan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2021)
The Two-Variable Linear Equation System (SPLDV) is one of the mathematics subject matter that requires a good understanding of the students. The Problems that occur when students are asked to solve problems in everyday situations involving SPLDV students feel this material is difficult to study. Students do not realize that the activity of the activities SPLDV generally been done by the students in their daily lives, but students do not have sufficient capacity to make and complete the mathematical model of the activities they do. To overcome the above problems needed an easier way, effective and close to the student habit is to Shopping Cart Games. With the Shopping Cart Games as activity in the class of VIII MTs Hamparan Perak, are increased in problem solving in everyday situations involving SPLDV. The increased activity of VIII D to solve problems in everyday situations involving SPLDV through Shopping Cart Games, known through observation of 3 (three) observer, who concluded that in the first cycle, the student activity only listen to the teacher's explanation and resolve the given problem students still has not been able to understand the concept of problems in everyday situations involving SPLDV primarily on the element A, the students themselves less able to communicate the results of his thinking, students are less active in reflective thinking, the value of the average student is still low at 53.47, the number of students who are not active> of in active, with 21 students who inactive and 15 students were active. In the second cycle, students are able to understand the concept of problems in everyday situations involving SPLDV primarily on the element A, the students have been able to communicate for themselves the results of thinking, students are already active in thinking reflective, students are able to increase the activity in handling problems in everyday situations related to SPLDV. In the second cycle the students have been able to interpret about the story, make a mathematical model more than one, completing in finished results, interpreting the finished results, check out the accuracy of finished result, ask questions and discuss.